Job-embedded, collaborative and reflective professional development for university administrators: The action learning pedagogy - Middlehurst, R.; Cross, M.; Jeannin, L. (South African Journal of Higher Education, 2018)
Job-embedded, collaborative, and reflective professional development programmes have generally been praised internationally for promoting knowledge sharing and meeting the learning needs of extremely busy practitioners, such as university academic and administrative staff. However, in the Southern African context where, for a variety of reasons, professional development draws extensively on traditional pedagogies, their usefulness has not been fully tested. Analysing the experiences of 11 participants of the Programme for University Leadership in the Southern African Region (PULSAR) and subsequent developments within their own institutions, this paper shows how Action Learning can be used as a tool for change for university senior administrators. Through this job-embedded, collaborative, and reflective pedagogy, Action Learning provides enabling conditions for university administrators to unlearn, learn and relearn engagement strategies (e.g., questioning and listening skills, participative team-work) to approach workplace problems differently, and in the process, build more effective working relationships.